Carborane Dyads for Photoinduced Electron Transfer: Photophysical Studies on Carbazole and Phenyl‐o‐carborane Molecular Assemblies. Issue 20 (12th May 2014) - Kwon, Soonnam; Wee, Kyung‐Ryang; Cho, Yang‐Jin; Kang, Sang Ook
Abstract o‐Carborane‐based donor–acceptor dyads comprising an o‐carboranyl phenyl unit combined with N‐carbazole (1) or 4‐phenyl‐N‐carbazole (2) were prepared, and their dyad characters were confirmed by steady‐state photochemistry and photodynamic experiments as well as electrochemical studies. The absorption and electrochemical properties of the dyads were essentially the sum of those of the carbazole and o‐carboranyl phenyl units; this indicates negligible interaction between the carbazole and o‐carborane units in the ground state. However, the emission spectra of 1 and 2 indicated that carbazole fluorescence was effectively quenched and a new charge‐transfer (CT) emission was observed in solvents, varying from hexane to acetonitrile, which exhibited large Stoke shifts. The CT emission properties of o‐carborane‐based dyads were further analyzed by using Lippert–Mataga plots to show that unit charge separation occurred to form a charge‐separated species in the excited state, namely, 1⋅2. This excited‐state species was confirmed by nanosecond transient absorption spectra and spectroelectrochemical measurements; the photoexcitation of carbazole generated the CT state in which a radical cation and anion were formed at the carbazole and o‐carborane units, respectively, within a few nanoseconds. DFT calculations corroborated the presence of this CT species and showed localized populations of the highest singly occupied molecular orbital on 2 in the reduced anionic state. As a result, molecular assemblies formed by linking the carbazole group with the o‐carborane cage through a phenylene or multi‐phenylene spacer revealed that the photoinduced electron‐transfer process occurred intramolecularly.